The importance of treating community-acquired pneumonia in children under 5 years of age (CAP) (Research, Society and Development, 2022)
Pneumonia, an infectious disease of the lower airways, is among the three main causes of morbidity and mortality children in developing countries. The objective was to discuss the importance of the treatment of Community Acquired Pneumonia (CAP) in children under 5 years old, describing the characteristics and antibiotic therapy, comparing the effectiveness of the drugs recommended by the WHO. Material and Method: This was an integrative literature review in LILACS, PUBMED/MEDELINE and SCIELO databases, between 2013 and 2022. 75 articles were identified, 10 of which were used in the elaboration of the work. Results show that CAP is the leading cause of death among infectious diseases that affect children. Its rapid identification is of paramount importance for the initiation of an adequate treatment and to avoid further complications or even death. Better access to effective prevention and management strategies is needed in low- and middle-income countries, while new strategies are needed to address the residual burden of disease once implemented.